"Binders of Bayonets for Big Bird": Analysis of Political Cartoon Images of the 2012 Presidential Debates. (August 2014) - Conners, Joan L.
Consistent with other media covering the 2012 presidential campaign, political cartoons attended to the events surrounding the three presidential debates between Mitt Romney and Barack Obama. While political cartoons offer a humorous visual commentary, they are part of the campaign media narrative, and are perhaps more memorable than many stories or columns themselves. This analysis discusses the attention to and portrayal of particular candidate performance in the 2012 presidential debates, and how particular statements or behavior was visually demonstrated in political cartoons, and also discusses the implication of such portrayals and attention in cartoons.